Optimalisasi Bekatul Beras Organik Menjadi Produk Cookies dan Sereal Sehat di Kelompok Tani Setia Budi Situbondo, Jawa Timur - Irsyam, Mahrus; Rian Fauziah , Riska; Nadzirah, Rufiani; Sholikhah, Ummi; Nu'maa Zahrani, Salma; Diamanta Devina , Clairine; Natasya Zulfikha, Salsa; Thalita Salsabila, Niken (Politeknik Negeri Jember, 2024)
Organic red rice has higher nutritional value compared to white rice and is increasingly favored as public awareness of healthy lifestyles grows. Kalianget Village in Situbondo is one of the regions producing organic red rice, managed by the Setia Budi Farmer Group. However, the marketing of these products is still limited due to a lack of innovation insufficient branding skills, and e-commerce utilization. This community service activity aims to provide training and assistance in revitalizing derivative products of organic red rice, namely cereal and cookies made from rice bran, while also enhancing the group's capabilities in branding and digital marketing. The program involved 20 members of the farmer group, 3 lecturers, and 4 students from the University of Jember. The stages of the activity included socialization, product-making training, branding and marketing training, packaging design assistance, and e-commerce implementation. The results showed an improvement in participants' skills in product diversification and digital marketing strategies. This training has generated promising business prospects for the group and is expected to enhance the competitiveness of their products in broader markets.